2022
DOI: 10.1021/acs.jchemed.2c00502
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of a Bioinfographic Assignment in Second-Semester Biochemistry: Metabolic Pathways beyond the Classroom

Abstract: Second-semester biochemistry students at two primarily undergraduate institutions, the California State Polytechnic University, Pomona, and the State University of New York College at Cortland, worked on a collaborative, semester-long project that resulted in the production of bioinfographics focused on metabolic pathways. Students were divided into seven metabolic pathway groups, and each student produced a 1-page bioinfographic where they detailed the structure, function, and broader impacts of a metabolic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The benefits of peer-assisted learning are well established and include advantages such as (i) providing better cognitive matches, (ii) establishing a sense of community, and (iii) enhancing learning for both parties. As such, we incorporated two modes of peer-assisted review, peer and near-peer, which revealed common challenges that advanced students experienced in curating infographics for a general audience. As seen in the pre- and postreview examples (Figure ), most students initially misgauged their target audience.…”
Section: Resultsmentioning
confidence: 99%
“…The benefits of peer-assisted learning are well established and include advantages such as (i) providing better cognitive matches, (ii) establishing a sense of community, and (iii) enhancing learning for both parties. As such, we incorporated two modes of peer-assisted review, peer and near-peer, which revealed common challenges that advanced students experienced in curating infographics for a general audience. As seen in the pre- and postreview examples (Figure ), most students initially misgauged their target audience.…”
Section: Resultsmentioning
confidence: 99%
“…Informational graphics, known as infographics, is another emerging medium that holds promise in an educational setting (as a teaching aid) and to help communicate science, given its general popularity in digital marketing. Infographics conveys data, information, or knowledge to non-experts in a visually appealing narrative by the clever use of concisely curated text and graphics. Many chemistry-themed infographics have already appeared to engage the general audience in the form of a Web site called Compound Interest created by Andy Brunning, which has attained over 107 K followers on Twitter under the handle @compoundchem. Several previous research studies have also reported the use of infographic creation to improve student engagement and communication skills in various chemistry courses. …”
Section: Introductionmentioning
confidence: 99%